Organizational Culture and Learning in Automobile Service Sector in Nepal - Amrit Dhakal (Surkhet Journal, 2025)
This research explores the factors that shape organizational learning culture and examines their impact on organizational learning within Nepal's automobile service sector. It aims to understand how elements such as organizational communication, rewards and incentives, innovation, worker involvement, and worker empowerment contribute to fostering a learning environment. The study adopted a causal comparative research design. Data were collected through a Google questionnaire targeting employees from various automobile-related companies. The sampling was conducted using a random sampling method and the size was determined using the solving method for unknown population. Statistical tools, correlation and regression were employed to analyze the data, ensuring a thorough evaluation of the relationships between the identified variables. The results reveal that organizational learning culture is strongly influenced by organizational communication, rewards and incentives, innovation, worker involvement, and worker empowerment. Together, these factors play a crucial role in creating an environment that supports continuous learning and development within organizations. The study concludes that organizations need to go beyond traditional training and development initiatives. Prioritizing factors such as effective communication, well-designed incentive systems, fostering innovation, and actively engaging employees enhances organizational learning culture. By doing so, managers are boosting employee performance while achieving long-term growth and profitability for their organizations.